Defect structure in δ-Bi5PbY2O11.5. Issue 17 (26th March 2019) - Borowska-Centkowska, Anna; Liu, Xi; Krynski, Marcin; Leszczynska, Marzena; Wrobel, Wojciech; Malys, Marcin; Hull, Stephen; Norberg, Stefan T.; Krok, Franciszek; Abrahams, Isaac
Abstract : Total neutron scattering analysis and ab initio MD simulations reveal details of oxide ion vacancy ordering and migration pathways. Abstract : A detailed study of the defect structure in a di-substituted δ-Bi2 O3 type phase, δ-Bi5 PbY2 O11.5, is presented. Using a combination of conventional Rietveld analysis of neutron diffraction data, reverse Monte Carlo (RMC) analysis of total neutron scattering data and ab initio molecular dynamics (MD) simulations, both average and local structures have been characterized. δ-Bi5 PbY2 O11.5 represents a model system for the highly conducting δ-Bi2 O3 type phases, in which there is a higher nominal vacancy concentration than in the unsubstituted parent compound. Uniquely, the methodology developed in this study has afforded the opportunity to study both oxide-ion vacancy ordering as well as specific cation–cation interactions. Oxide-ion vacancies in this system have been found to show a preference for association with Pb 2+ cations, with some evidence for clustering of these cations. The system shows a non-random distribution of vacancy pair alignments, with a preference for 〈100〉 ordering, the extent of which shows thermal variation. MD simulations indicate a predominance of oxide-ion jumps in the 〈100〉 direction.